The effect of classical guidance services and individual services on students motivation to continue to college - Kusnawati, Rini; Dewi, Muharika; Fitria, Riana Agus (Research in Education and Technology (REGY), 2024)
This research aimed to determine the measurement of the influence of classical tutoring services and individual services on guidance and counseling (BK) teaching methods in high schools in providing motivation for students to continue their education to college. The research method was carried out through distributing research questionnaires about classical services, individual services on student motivation. After the questionnaire results were collected and tabulated, analysis was then carried out using the multiple regression analysis method using SPSS 20. The research results revealed that classical services and individual services partially (together) had an influence on student motivation with a large influence. Still in the weak interval, with the classical service variable not having a significant influence.